Considerations on dialectic - Salazar Paniagua, Freddy (Estudios de Filosofía, 1992)
The article gives an exposition of Hegel’s thesis on dialectic as the only true method of philosophy, as opposed to the analytical method proper to the rationallism of the Enlightenment; it malees reference to the important correctives the former makes on the latter, in a contempornry view.